The Cross and Reaganomics Conservative Christians Defending Ronald Reagan - Crouse, Eric Robert, 1960- (Lanham, Maryland : Lexington Books, 2013)
The Cross and Reaganomics: Conservative Christians Defending Ronald Reagan, by Eric R. Crouse, offers important insights on why Reaganomics was a major reason conservative Christians supported Reagan at the polls. They embraced and tapped into the traditional American values of individual opportunity, personal responsibility, and human freedom- all themes they believed were front and center in Reaganomics. Conservative Christians were, indeed, among the most consistent champions of limited government, free enterprise (particularly sma
The rise of free market solutions -- Christians debating capitalism -- Economic recovery -- A sense of political purpose -- Cold War matters -- The final accounting.
Includes bibliographical references and index.
Description based on print version record.
Keywords: United States -- Economic policy -- 1981-1993.; Christian conservatism -- United States; Religious right -- United States; United States -- Politics and government -- 1981-1989.; BUSINESS & ECONOMICS / Economics / General; BUSINESS & ECONOMICS / Reference; Electronic books